Optimalisasi Moderasi Beragama dalam Menunjang Terwujudnya SDG's Berbasis Kearifan Lokal Masyarakat Bugis - Kamila, Adinda Nurul; Astuti, Astuti (Adaara: Jurnal Manajemen Pendidikan Islam, 2024)
Indonesia as a multicultural and multireligious country is one of the gifts as well as problems that are often feared to cause multiple interpretations that cause divisions between tribes or even religions. This study aims to determine the application of religious moderation in educational institutions, to find out the concept of local wisdom of the Bugis community, to determine the correlation of Islamic education with local wisdom of the Bugis community, to find out the optimization of religious moderation in supporting SDG's based on local wisdom of the Bugis community. The type of research that the author used in this study was qualitative research. Qualitative research is a study aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually and in groups. The approach used in this study is a sociological approach and a psychological approach. This research was conducted at SMA Negeri 13 Bone. The data analysis is carried out in stages; data reduction, completing the selection of collected data based on the relevance of the research topic; presentation of data, displaying data according to the problems discussed in this study; and verification or drawing conclusions, making corrections and checking with relevant sources and journals so that conclusions can be made. The results showed a lack of student understanding related to religious moderation, so optimization, introduction and socialization to students are needed in order to be able to understand religious moderation well as supporting the realization of SDG's.